1997
DOI: 10.1111/j.1365-2222.1997.tb02987.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic reactions to ampicillin. Studies on the specificity and selectivity in subjects with immediate reactions

Abstract: Although AMP can induce an immediate IgE response in subjects allergic to betalactams and the structure of the side chain may contribute to the specificity of the response, our results indicate that in most instances crossreactivity with the other penicillins exists and that in the groups studied selective reactions to just AMP derived determinants were uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Similarly, because we did not test for a wide variety of penicillin side-chain reactions, we can only draw conclusions about reactions caused by the major and minor determinants of penicillin. However, there is considerable crossreactivity between ampicillin and these determinants [18].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, because we did not test for a wide variety of penicillin side-chain reactions, we can only draw conclusions about reactions caused by the major and minor determinants of penicillin. However, there is considerable crossreactivity between ampicillin and these determinants [18].…”
Section: Discussionmentioning
confidence: 99%
“…A DP of tetracycline, i.e., epianyhdrotetracycline, causes Fanconi's syndrome leading to renal failure [5]. Another example is that of polymeric DPs in aminopencillins that have been attributed to cause allergenicity and not the drugs themselves [6,7]. The most recent case is the presence of oversulfated chondroitin sulfate in heparin samples that caused allergenic reactions and over 100 deaths [8].…”
Section: The Focus On Impurities and Degradation Productsmentioning
confidence: 98%
“…A recent study of 48 Italian subjects with IgE-mediated allergic reactions to ampicillin found that only three (6.25 %) cases were selective reactors [35]. IgE allergic selective reactions to penicillin V [36][37][38], cloxacillin [39,40], and piperacillin [41,42] have also been reported for a limited number of cases.…”
Section: Penicillin As An Alternative Treatmentmentioning
confidence: 99%